Production in Islam: An Analysis for the Convection SMEs Development - Rahasia Taufiqi Al-Ayyubi; Richa Angkita Mulyawisdawati (Cakrawala: Jurnal Studi Islam, 2021)
Islamic production is one of the production behavior solutions that can be used as a model for developing people's abilities and creativity while maximizing available resources. This study, carried out by Simpati Convection, Sidoarjo, aims to identify Islamic production factors according to Abdul Manan and Islamic production behavior according to Yusuf Qaradhawi. A phenomenological study is used in this qualitative research design. Simpati's convection business practice was found to be in line with Abdul Manan's concept in terms of production factors and Qaradhawi in terms of production behavior, according to the findings. This Islamic business process has gone through a long period of development, with usury funds being used as capital at the outset. In terms of production behavior, Simpati Convection is committed to the halal principle, strives for people's prosperity and independence, and believes in lifelong learning.